Debates in the Digital Humanities - Gold, Matthew K. (University of Minnesota Press, 2012)
Debates in the Digital Humanities brings together leading figures in the field to explore its theories, methods, and practices and to clarify its multiple possibilities and tensions. Together, the essays-which will be published later as an ongoing, open-access website-suggest that the digital humanities is uniquely positioned to contribute to the revival of the humanities and academic life.